Topographical variation in glycosaminoglycan content in human articular cartilage. - Rogers, B; Murphy, C; Cannon, SR; Briggs, T (2006)
The weight-bearing status of articular cartilage has been shown to affect its biochemical composition. We have investigated the topographical variation of sulphated glycosaminoglycan (GAG) relative to the DNA content of the chondrocyte in human distal femoral articular cartilage. Paired specimens of distal femoral articular cartilage, from weight-bearing and non-weight-bearing regions, were obtained from 13 patients undergoing above-knee amputation. After papain enzyme digestion, spectrophotometric GAG and fluorometric DNA assays assessed the biochemical composition of the samples. The results were analysed using a paired t-test. Although there were no significant differences in cell density between the regions, the weight-bearing areas showed a significantly higher concentration of GAG relative to DNA when compared with non-weight-bearing areas (p = 0.02). We conclude that chondrocytes are sensitive to their mechanical environment, and that local loading conditions influence the metabolism of the cells and hence the biochemical structure of the tissue.